2006
DOI: 10.1111/j.1440-1746.2006.04268.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between hepatitis A virus and Helicobacter pylori in a developing country: The saga continues

Abstract: The low number of subjects negative for both H. pylori and HAV antibodies in Lebanon is indicative of their high prevalence in the country. It is possible that this high prevalence reflects an age-specific prevalence rather than a true association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Our study showed an opposite picture, whereby there was a very low seroprevalence rate of HAV and a moderately high rate of H. pylori . Our study is similar to many other studies [17–19,26–30] in that H. pylori and HAV were not significantly associated. This adds further proof that H. pylori and HAV do not share a common transmission route and source as previously believed.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed an opposite picture, whereby there was a very low seroprevalence rate of HAV and a moderately high rate of H. pylori . Our study is similar to many other studies [17–19,26–30] in that H. pylori and HAV were not significantly associated. This adds further proof that H. pylori and HAV do not share a common transmission route and source as previously believed.…”
Section: Discussionsupporting
confidence: 92%
“…The association of serum antibodies against H. pylori with serum antibodies against two known waterborne pathogens hepatitis A virus [18] and Giardia [19] suggests that the infection may be waterborne or related to poor sanitary practices [20]. Klein et al [21] studied the prevalence of H. pylori infection in 407 children (two months to 12 years old), in Lima, Peru.…”
Section: Resultsmentioning
confidence: 99%
“…Since H. pylori is transmitted from person-to person suggesting fecal to oral transmission, 18 several investigators have studied a possible link between seropositive H. pylori and HAV. [19][20][21] In our study, HAV seropositivity was significantly higher in the H. pylori-positive group suggesting the possible association between both infections. The socioeconomic status is presumed to play an important role in H. pylori infection, 22 which was one of the associated factors with HAVseropositivity in our study.…”
Section: Discussionmentioning
confidence: 99%